Lipidome and proteome map of myelin membranes12. Issue 3 (27th November 2012) - Gopalakrishnan, Gopakumar; Awasthi, Anshul; Belkaid, Wiam; De Faria, Omar; Liazoghli, Dalinda; Colman, David R.; Dhaunchak, Ajit S.
Abstract To understand the molecular anatomy of myelin membranes, we performed a large‐scale, liquid chromatography‐coupled tandem mass spectrometry (LC‐MS/MS)‐based lipidome and proteome screen on freshly purified human and murine myelin fractions. We identified more than 700 lipid moieties and above 1, 000 proteins in the two species, including 284 common lipids and 257 common proteins. This study establishes the first comprehensive map of myelin membrane components in human and mice. Although this study demonstrates many similarities between human and murine myelin, several components have been identified exclusively in each species. Future quantitative validation studies focused on interspecies differences will authenticate the myelin membrane anatomy. The combined lipidome and proteome map presented here can nevertheless be used as a reference library for myelin health and disease. © 2012 Wiley Periodicals, Inc.